The Implementation of Teachers' Indirect Feedback on Students' Writing Performance in Descriptive Text - Febriani, Elvina; Pujiawati, Nia; Fitriyana, Wahyudin (PROJECT (Professional Journal of English Education), 2026)
This study aims to describe the implementation of teachers’ indirect feedback on students’ descriptive writing skills and to examine how this feedback contributes to improving their grammatical accuracy. The research was conducted at one of the state junior high schools in Karawang Regency, Indonesia, involving seventh-grade students as participants. A qualitative approach with a case study design was employed to allow an in-depth exploration of the feedback process within a real classroom context. Data were collected through classroom observations, interviews, and analysis of students’ writing drafts before and after the application of indirect feedback. The findings revealed that the use of indirect feedback effectively helped students identify and correct grammatical errors, particularly in areas such as subject-verb agreement, verb tense, and word choice. As a result, students demonstrated noticeable improvement in their overall writing quality and grammatical accuracy. Moreover, the students expressed positive attitudes toward this feedback technique, stating that it motivated them to revise their work and encouraged greater independence in learning. The novelty of this study lies in its focus on implementing indirect feedback in junior high school settings, especially in teaching descriptive texts, which remains an underexplored area in Indonesian EFL contexts.